2017
DOI: 10.1080/21645515.2017.1397243
|View full text |Cite
|
Sign up to set email alerts
|

Revaccination against hepatitis B in late teenagers who received vaccination during infancy: Yes or no?

Abstract: The significance of vaccination against hepatitis B during infancy is recognized worldwide, however, whether booster or revaccination after a period of time following the primary vaccination is required remains controversial. Recently, cross-sectional epidemiological surveys found that HBsAg prevalence in subjects born after the implementation of mass vaccination was increased with age, which was attributed to waning of anti-HBs over time. However, comprehensive analysis of the closely related cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…In the Urganci et al study [12], the period after vaccination was 4 weeks, and the time was not reported in studies by Watts et al [10] and Moses et al [11]. It is documented that in immunocompetent individuals who are fully vaccinated against HBV, protective serologic titers may persist for more than 20 years, and no booster dose is recommended [15]. However, in immunosuppressed patients such as patients with IBD, the velocity of antibody weaning is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In the Urganci et al study [12], the period after vaccination was 4 weeks, and the time was not reported in studies by Watts et al [10] and Moses et al [11]. It is documented that in immunocompetent individuals who are fully vaccinated against HBV, protective serologic titers may persist for more than 20 years, and no booster dose is recommended [15]. However, in immunosuppressed patients such as patients with IBD, the velocity of antibody weaning is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Such evidence acquires significance in an occupationally exposed population at greater risk for HBV. As recently pointed out by the review of Zhao and Zhou [31], whether booster or revaccination after a period of time following the primary vaccination is required remains a debated issue. Nonetheless a booster response could be observed in most of subjects vaccinated 30 years ago, as confirmed by breakthrough HBV infection with severe consequences in successfully vaccinated individuals is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…Although transient infection was infrequently documented, no new HBV carrier cases were identified in the 10‐year follow‐up study from Italy, the 20‐year follow‐up study from Thailand, and the 30‐year follow‐up study from Alaska . Two reviews of long‐term studies show that chronic HBV infection is an extremely rare event in successfully vaccinated individuals . These findings strongly suggest that a routine booster vaccine is not necessary if an adequate anti‐HBs level, ≥10 mIU/m, is achieved once.…”
Section: Why Is a Routine Booster Dose Of Hb Vaccine Unnecessary?mentioning
confidence: 99%